Peningkatan Pengetahuan Kader Posyandu dalam Penggunaan Buku KIA - Eli Rahmawati; Ernani Setyawati; Novia Nurhasanah (Poltekita: Jurnal Pengabdian Masyarakat, 2020)
In an attempt to accelerate the decline of AKI and AKB, the health sector made a breakthrough using the Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K), midwifemedicaster relations, the utilization of MCH, and the practical revitalization of Pemantauan Wilayah Setempat Kesehatan Ibu Anak (PWS KIA). The role of health service workers in the practice of Integrated Service Posts are crucial. Alas, a huge number of health service workers have the lack of comprehension and skills in regards of doing their tasks. The purpose of social service is to identify the characteristics of the Integrated Health Service workers that take parts in social service (i.e. Age, Education Level, and their tenure as health services workers). Efforts regarding the development of the service workers’ comprehension of KIA books, and the effectiveness of MCH books towards society, particularly health service workers. The methods used are lectures and discussions. the results gained from the participants are as follows: Ages in the range of 27-63 years, Tenures in the range of 2-32 years, and Education Levels in the range of Junior high-university graduates. The numerical mean for pretest is 48.57 and for post test is 64.89. An increased number of mean had been achieved by 16.33. This result concludes that education may develop the comprehension of health service workers in the utilization of MCH book.